Manajemen Layanan Khusus Kesehatan Dalam Persiapan Pembelajaran Tatap Muka Era New Normal di Madrasah Tsanawiyah Negeri 2 Probolinggo - Ahmad, Niswatin (Cendekia : Jurnal Pendidikan dan Keagamaan, 2024)
A pandemic situation like this maintains health, maintaining cleanliness and immunity is an important option for survival. Without exception, educational institutions always ensure that students, teachers and madrasah residents remain comfortable, healthy and comply with health protocols which play a role in meeting health needs. The focus of the research studied included: planning, implementation and evaluation of special health service management in preparation for face-to-face learning in the new normal era. The aim of this research is to describe the planning, implementation and evaluation of special health service management in preparation for face-to-face learning in the new normal era at MTsN 2 Probolinggo. This research uses qualitative research methods with a case study type. The data collection techniques use observation, interviews and documentation. Data analysis starts from the data collection stage. Data condensation, data withdrawal and conclusion drawing. Meanwhile, data validity uses technical triangulation and source triangulation. The results of this research include: 1) Special health service management planning in preparation for face-to-face learning in the new normal era including needs analysis, program preparation, needs budget, monitoring needs services; 2) Implementation of special health service management in the division of tasks involving madrasa heads, educators, UKS heads, UKS member teachers, cleaning officers, the MTsN 2 Probolinggo task force team and always coordinating with the Covid-19 task force team and the Pajarakan Community Health Center; 3) Evaluation of special health service management in preparation for face-to-face learning in the new normal era includes weekly evaluations, namely controlling health protocol facilities and infrastructure, monthly evaluations, namely performance assessment and monitoring of health protocols.